1989
DOI: 10.1002/jmv.1890290211
|View full text |Cite
|
Sign up to set email alerts
|

Passive protection of mice, goats, and monkeys against Japanese encephalitis with monoclonal antibodies

Abstract: Six monoclonal antibodies (McAbs) against Japanese encephalitis virus (JEV) were tested for passive protection in JEV-infected mice, goats, and rhesus monkeys. mG9 and nG2 had no protective effect; mG3 and 2D2 had some protective effect, but not sufficient to be of therapeutic significance; and 2H4 and 2F2 had excellent protective efficacy in mice even 120 hr after infection when most of the mice in the virus control group were sick. The mixture of 2H4, 2F2, mC3 (M-McAb), and their F(ab')2 fragments showed exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…However, the E protein plays a dominant role in generating neutralizing antibodies and providing protective immunity in the host. Passive transfer of JEV E-specific neutralizing MAbs has been shown to protect recipients from JEV-induced fatal encephalitis (3,16,32,55). Antigenic and structural analysis using various panels of MAbs has shown that most of the E protein epitopes that elicit virus-neutralizing antibodies are conformationally dependent (9,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the E protein plays a dominant role in generating neutralizing antibodies and providing protective immunity in the host. Passive transfer of JEV E-specific neutralizing MAbs has been shown to protect recipients from JEV-induced fatal encephalitis (3,16,32,55). Antigenic and structural analysis using various panels of MAbs has shown that most of the E protein epitopes that elicit virus-neutralizing antibodies are conformationally dependent (9,40).…”
Section: Discussionmentioning
confidence: 99%
“…Tenmicroliter aliquots of the cell suspension were then spotted onto slides, air dried, and fixed with acetone at 4°C for 10 min. Immunofluorescent mapping of the E protein-specific epitopes was performed using a panel of murine monoclonal antibodies (MAbs) (15,42,55) and JEV-specific hyperimmune mouse ascitic fluid (HIAF). All antibodies were tested at 1:400 dilution in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…However, this challenge model does not cause encephalitis in monkeys; therefore, it does not allow demonstration of protection against disease. 5,[27][28][29] Direct intraspinal and intrathalamic inoculations of JEV in rhesus monkeys result in rapid fatal infection within seven days, 5 but a challenge model by these routes is very severe. The intranasal challenge used in this study represents a noninvasive peripheral route of inoculation that predictably produces clinical signs similar to those found in humans with JE.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of a vigorous, virus-specific, humoral immune response in ameliorating and preventing illness has been documented in human cases of JE Libraty et al, 2002;McCallum, 1991) and in animal models by administration of antibody prior or subsequent to infection with JEV (Goncalvez et al, 2008;Gupta et al, 2003;Kimura-Kuroda & Yasui, 1988;Zhang et al, 1989). We have shown that mice genetically defective in B cells and antibody ( MT-/-) develop uncontrolled viremia, viral persistence in peripheral tissues, rapid and widespread viral dissemination into the CNS, and early uniform mortality (Larena et al, 2011).…”
Section: B Cellsmentioning
confidence: 99%